A big data and cloud computing specification, standards and architecture: agricultural and food informatics. (2019) - Li, Na; Mahalik, Nitaigour Premchand
Big data has gone from emerging to a widely used technology in industrial, commercial, research, and database applications. It is used for processing and analysing massive sets of data to derive useful patterns, inferences, and relations. The real-time data storage and management architecture plays important role. This paper introduces big data, includes the background and definitions, characteristics, related technologies, and challenges associated with implementing big data-based application technologies. This paper also introduces cloud computing, a related yet independent emerging technology and includes the modern technologies and standards, definitions, service and deployment models, advantages and challenges, and development prospects. The paper considers computing specification, standardised procedure, and system architecture in regard to big data systems and cloud computing.